2000
DOI: 10.1063/1.125650
|View full text |Cite
|
Sign up to set email alerts
|

Quantum confinement of E1 and E2 transitions in Ge quantum dots embedded in an Al2O3 or an AlN matrix

Abstract: Alternating layers of Ge quantum dots embedded in either Al2O3 or AlN matrices were deposited on sapphire substrates by pulsed-laser deposition. The characteristics of the dots are shown to be independent of the surrounding matrix. The dots size (73, 130, 160, and 260 ű5%) was controlled by the laser energy density and deposition time, and was characterized by high-resolution transmission electron microscopy. The dots were single crystalline with no apparent GeOx interfacial layers. Transmission spectroscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 17 publications
2
18
0
Order By: Relevance
“…[6][7][8][9] Germanium QDs embedded in amorphous wide-band-gap matrices like SiO 2 or Al 2 O 3 have numerous interesting properties such as very strong quantum confinement, electroluminescence and photoluminescence, nonlinear refraction index, possibility to retain electric charge for long time, etc. [10][11][12][13][14][15][16] Therefore they have great possibilities for application in nanotechnology, especially for QD-based memories, sensors and solar cells. Recent investigations showed that Al 2 O 3 matrix has many advantages compared to usually used fused silica, since alumina has a higher dielectric constant, excellent thermal and mechanical properties and it is more suitable as a building material for gates in memory devices.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] Germanium QDs embedded in amorphous wide-band-gap matrices like SiO 2 or Al 2 O 3 have numerous interesting properties such as very strong quantum confinement, electroluminescence and photoluminescence, nonlinear refraction index, possibility to retain electric charge for long time, etc. [10][11][12][13][14][15][16] Therefore they have great possibilities for application in nanotechnology, especially for QD-based memories, sensors and solar cells. Recent investigations showed that Al 2 O 3 matrix has many advantages compared to usually used fused silica, since alumina has a higher dielectric constant, excellent thermal and mechanical properties and it is more suitable as a building material for gates in memory devices.…”
Section: Introductionmentioning
confidence: 99%
“…Blue shifts and splittings of the E 1 and E 2 transitions were measured in GaAs/AlAs superlattices 3,4 . More recently, a quantum confinement induced shift of E 1 and E 2 was measured in Ge nanoparticles embedded in a glassy matrix 5,6 . A main purpose of this work is to calculate the behavior of E 1 and E 2 transitions upon confinement in GaAs/AlAs superlattices and in free-standing GaAs layers, which are simulated by GaAs/vacuum superlattices.…”
Section: Introductionmentioning
confidence: 99%
“…9 The height sizes of our QDs are permissible to expect the quantum confinement effect. 8 Therefore the observed blue shift is determined by the interplay between above two effects.…”
Section: ωmentioning
confidence: 97%